Social accountability mechanism and customer satisfaction: Findings from the study of Padang Jawa Road Transport Department, Selangor, Malaysia / Marni Ghazali - Marni, Ghazali (2018)
Good governance has long been a topic of discussion in Malaysia as in many other countries. In fact, it became a world-wide phenomenon in many aspects of life either for public sector, private sector, society, non-profit organisation and international institutions. Generally, the aim of good governance is to increase development effectiveness, improved governance and also to enhance citizen empowerment (Malena et al., 2004; Siddiquee et al., 2010). In recent times, interest in good governance practices within Asian countries and in any other countries has also increased. the empirical findings of this study would assist other government departments which plan to adapt social accountability practices in their organization. Perhaps it could be extended to other government agencies that practice these mechanisms to see how the public officials and service users perceived the influence and perhaps the effect of a meet customer day (public hearing), customer feedback forms (citizen report cards) and customer charter (client charter) towards achieving maximum level of satisfaction.